Web Profile Design for Al-Muttaqien Mosque using Agile Method - Putri Sabilla Br Tarigan; Johanes Terang Kita Perangin Angin; Hendri (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of information technology in today’s digital era has had a major impact in various aspects of people’s lives, including in terms of disseminating religious information. Al-Muttaqien Mosque located in Delitua still uses conventional methods in delivering information and managing its religious activities. This causes a lack of fast and efficient access to important information for worshipers, such as activity schedules, ustaz searches, or funeral arrangements. This study aims to design and build a mosque profile website as a more modern and structured information media. This website includes general mosque information, activity schedules, religious news, and board contacts. With this website, it is expected that the delivery of information will be easier, faster, and reach the community at large.The system development method used is the Agile method, which is iterative, flexible, and adaptive to change. Agile was chosen because it is able to accelerate the development process and allows for regular evaluation and improvement during the website development process. The process was carried out in several sprints with a focus on user needs and core system functionality.The final result of this research by Al-Muttaqien Mosque profile website that has been successfully implemented and hosted online. This website can be accessed by worshipers and the general public as an effective medium of communication and information, and is expected to be the first step in digitizing mosque services in the future.